SEMANTICS AND PRAGMATICS OF MODERN MEDIA FROM THE PERSPECTIVE OF MANIPULATIVE EFFECT ON GENERATION Z (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-30-42Pragmalinguistic analysis of media texts with a destructive component (violence, suicide, revenge, reprisals) is presented. A feature of the media content under study is: 1) the presence of a digital communicator – a digital platform (blog, messenger, social network, video, etc.) for broadcasting and replicating the communication process by the participants themselves (representatives of generation Z); 2) the place and role of a digital communicator in the implementation of a given destructive behavioral model. The transformation of axiosphere was revealed: there were axiological shifts in the conceptual field "LIFE-DEATH". Due to it we were able to identify the potential activity of the destructive vector of the homo digitalis behavioral model. The "axiologeme" is interpreted by us as a speech signal of hidden influence. In the text it acts as a lexical unit with code evaluation, which forms positive, neutral or negative associations: death (negative in psychological and emotional terms; neutral (logical conclusion of the life way) from the point of view of Christian morality in objective reality, neutral in virtual reality, as it is possible to reboot and positive (receiving bonuses: likes, discussions, comments). The development of influence plans ("positive-approving, neutral-indifferent or negativedisapproving") for the described events allowed us to identify the author's assessment of the media text with a destructive component. Positive-approving plan – 36.4%, negative-disapproving - 46.1%, and neutral-indifferent – 18.5%. These data reflect the prospects for the preservation/non-preservation of the axiosphere of Russian linguaculture.Key words: axiosphere, axiologeme, homo digitalis, conceptual field "LIFE-DEATH", author's evaluation